Multidisciplinary Rehabilitation after Hyaluronic Acid Injections for Elderly with Knee, Hip, Shoulder, and Temporomandibular Joint Osteoarthritis - Lorenzo Lippi; Martina Ferrillo; Alessio Turco; Arianna Folli; Stefano Moalli; Fjorelo Refati; Luca Perrero; Antonio Ammendolia; Alessandro de Sire; Marco Invernizzi (Medicina, 2023)
Osteoarthritis (OA) is a prevalent degenerative joint condition characterized by cartilage deterioration, joint inflammation, and functional limitations, particularly impacting the elderly population. Rehabilitation and hyaluronic acid (HA) injections are common therapeutic approaches routinely used in clinical practice, but their synergistic potential is far from being fully characterized. Thus, the aim of this narrative review was to elucidate the multilevel benefits and synergies of integrating these two approaches in multidisciplinary OA rehabilitation. This narrative review follows the scale for the assessment of narrative review articles (SANRA) criteria and involves a comprehensive literature search from July to August 2023. Two independent reviewers screened studies, including those involving human subjects with OA, rehabilitation strategies, and outcomes following HA injection, published in English. Results: HA injections might improve joint biomechanics, reducing friction, absorbing shocks, and potentially regulating inflammation. Rehabilitation plays a pivotal role in strengthening muscles, increasing the range of motion, and enhancing overall function. Optimizing rehabilitation following HA injection might provide additional benefits in joint health. OA management requires a multidisciplinary approach integrating HA injections, rehabilitation, and personalized care. Challenges in patient adherence and healthcare resources currently exist, but emerging technologies offer opportunities to enhance patient engagement and monitoring optimizing sustainability and outcomes of patients with knee, hip, shoulder, and temporomandibular joint OA.